Protecting Consumer Rights in the Sharing Economy - Practice through the Airbnb Tourist Accommodation Sharing Model - Thinh, Duong Quoc; Phuong, Nguyen Thanh; Van, Tran Thi Thu; Huyen, Dinh Tran Ngoc; Khoe, Tran Thanh; Dinh, Nguyen Van (Journal of Ecohumanism, 2024)
The sharing economy (sharing economy) is known as a new business model compared to Vietnam and brings many benefits to the economy and society. The Vietnamese Government has initially recognized this business model and officially approved the "Project Proposal for Sharing Economic Model" which covers many fields. Besides the field of transportation, brands that can be easily known as Grab, Goviet, Be, in the field of accommodation services, there is the AirBnB model, housing sharing with the participation of many hotels and establishments. storage facility. These two areas are also the content that the topic provides the sharing economics subject to approach. AirBnB’s business model in Vietnam has brought many benefits to both renters and renters. However, it also poses less public risk to users, and the issue of guardians using services in the shared economy is a matter of concern. This study analyzes the practice of AirBnB’s business model from a legal perspective with the goal of clarifying the relationships and responsibilities of the entities participating in the model, especially the responsibility to protect human rights. Consumers then come up with publishing topics that are proposed to relevant parties.